The idea of the book in the Middle Ages: language theory, mythology, and fiction - Gellrich, Jesse M. (Cornell University Press, 2019)
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- ABBREVIATIONS -- [1] The Argument of the Book : Medieval Writing and Modern Theory -- [2] The Semiology of Space in the Middle Ages: On Manuscript Painting, Sacred Architecture, Scholasticism, and Music -- [3] The Language of Mythology : On Medieval Grammar and Hermeneutics -- [4] Dante's Liber Occultorum and the Structure of Allegory in the Commedia -- [5] The Origin of Language Reconsidered : Chaucer's House of Fame -- [6] Problems of Misreading: The "Prologue" to The Legend of Good Women -- [7] I nterpreting the "Naked Text" in the "General Prologue" to The Canterbury Tales -- [8] Retrospect: On Historical Change -- BIBLIOGRAPHY -- INDEX